2021
DOI: 10.1002/jsfa.11233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth‐stage‐based limited irrigation management on the growth, yields, and radiation utilization efficiency of winter wheat in northwest China

Abstract: BACKGROUND: As a common abiotic stress, water deficit stress has a negative impact on the growth and yield of many field crops worldwide. In this study, a mobile rain shelter experiment was conducted in the 2017-2019 growing seasons to investigate the effects of water stress at different growth stages on various traits in winter wheat, including plant height, leaf area index (LAI), biomass, radiation use efficiency (RUE), leaf photosynthetic traits, and yield. RESULTS: Three different limited irrigation treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The soil water status at different growth stages have different effects on the photosynthetic, physiological characteristics, and grain yield [ 19 , 20 ]. Cao et al [ 21 ] showed that winter wheat irrigated at the heading and grain-filling stages have a higher grain yield because of the largest leaf vitro rate of water loss, Gs and leaf water potential. Xue et al [ 22 ] reported that irrigation between jointing and anthesis periods significantly increased wheat yield by increasing photosynthesis and remobilizing pre-anthesis carbon reserves.…”
Section: Effects Of Irrigation Management On Wheat Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The soil water status at different growth stages have different effects on the photosynthetic, physiological characteristics, and grain yield [ 19 , 20 ]. Cao et al [ 21 ] showed that winter wheat irrigated at the heading and grain-filling stages have a higher grain yield because of the largest leaf vitro rate of water loss, Gs and leaf water potential. Xue et al [ 22 ] reported that irrigation between jointing and anthesis periods significantly increased wheat yield by increasing photosynthesis and remobilizing pre-anthesis carbon reserves.…”
Section: Effects Of Irrigation Management On Wheat Physiologymentioning
confidence: 99%
“…Wu et al [ 28 ] stated that water scarcity during flowering and grain-filling stages can inhibit and reduce photosynthesis and increase leaf senescence, which may diminish the contribution of pre-anthesis assimilates to yield. Some researchers found that no irrigation at the reviving and jointing stages could improve leaf photosynthetic traits by increasing Gs, Fv/Fm, and the effective quantum yield of PS II (Φ PSII ), thus increasing grain yield [ 21 ].…”
Section: Effects Of Irrigation Management On Wheat Physiologymentioning
confidence: 99%
“…Research indicates that drip irrigation leads to increased root density in wheat plants, facilitating enhanced root water and nutrient absorption, and consequently improving crop productivity [12,13]. Moreover, drip irrigation contributes to bolstering crop photosynthesis, promoting dry matter accumulation, and ultimately boosting crop productivity [14][15][16]. Micro-sprinkler irrigation, another water-saving micro-irrigation method, has been shown to elevate the chlorophyll content of winter wheat, retard leaf aging, enhance net photosynthetic rate and electron transfer in photosynthesis, and diminish intercellular CO 2 concentration, transpiration rate, and leaf stomatal conductance, thereby furnishing ample dry matter for grain formation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing irrigation frequency under drip irrigation sustains high moisture, especially in upper soil layers, and enhances crop productivity (Fang et al, 2018). Drip irrigation is conducive to saving irrigation water and in the improvement of dry matter accumulation, crop photosynthesis, and ultimately crop productivity (Cao et al, 2021;Li et al, 2021;Yan et al, 2022). In a comparison of drip irrigation with border irrigation by Yang et al (2020), it was noticed that drip irrigation decreased soil evaporation, transpiration, and wheat evapotranspiration by 18.5, 22 mm, and 3.5 per year, respectively.…”
Section: Introductionmentioning
confidence: 99%